2020
DOI: 10.3390/pharmaceutics12020187
|View full text |Cite
|
Sign up to set email alerts
|

Formulating a Stable Mannitol Infusion while Maintaining Hyperosmolarity

Abstract: Mannitol infusion is commonly used in the treatment of intracranial hypertension following traumatic brain injury. It has long been known to have stability issues, specifically, mannitol recrystallises from solutions greater than 10% w/v in ambient conditions. This can happen at any time, whether on the pharmacy shelf or during a medical procedure. This study describes the stability limits of 20% w/v mannitol infusion (the most common strength used clinically) and proposes a number of safer, stable and tuneabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The literature describes several crystalline forms of D-mannitol. While comparing the positions of diffraction peaks of D-mannitol in Figure 5 with the literature data, we concluded that the studied D-mannitol has the β-crystalline form [ 48 ].…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The literature describes several crystalline forms of D-mannitol. While comparing the positions of diffraction peaks of D-mannitol in Figure 5 with the literature data, we concluded that the studied D-mannitol has the β-crystalline form [ 48 ].…”
Section: Resultsmentioning
confidence: 79%
“…Diffraction peaks of crystalline inclusions in NP–XL according to their positions could be attributed to D-mannitol in δ-crystalline form [ 48 ]. We determined the crystalline inclusion content in the NP–XL, which was 8%, via the ratio of the overall integrated intensity of crystalline diffraction peaks to the integrated intensity of the diffuse X-ray scattering; the average size of crystalline inclusions in NP–XL, determined by the analysis of diffraction line width, was 25–35 nm.…”
Section: Resultsmentioning
confidence: 99%
“…D-mannitol solutions can be highly supersaturated by cooling, 15 , 22 and the metastable zone width (MSZW) of D-mannitol is narrow across a wide temperature range 14 suggesting that the 1 M D-mannitol at 4°C exceeds the critical supersaturation of D-mannitol for nucleation. Indeed, we observed D-mannitol crystallization in 2 weeks in the absence of additives ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“… 14 D-mannitol is also a commonly used osmotic diuretic treatment to manage fluid build-up conditions (e.g., cerebral edema, increased intracranial pressure) in the medical industry. 15 In addition, D-mannitol is a popular excipient in solid formulations to stabilize active pharmaceutical ingredients in the pharmaceutical industry. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Mannitol is slightly acidic (pH 6.3); thus it requires additional alkaline components in proprietary preparations for adjustment of pH and usually, sodium carbonate is used [26]. The solutions of mannitol (>10% w/v), if kept at room temperature, show the appearance of crystals but can be solubilized by increasing the temperature [27]. For example, the solubility of mannitol at 14 and 25 °C is 13% and 18% w/v [28,29].…”
Section: Introductionmentioning
confidence: 99%